Maximizing seed yield and economics through stem-training interventions in indeterminate tomato (Bangladesh Journal of Botany, 2026)
The study was carried out under open-field conditions to explore the impact of stem training on indeterminate tomato cultivar (Solan Lalima) during 2023 and 2024. The treatment comprised of three levels of training system (i.e., two, four and no stem. The results revealed that a two-stem training system improved the phenological traits, viz., plant height, number of flowers and fruits/cluster, enhanced fruit setting by 35% coupled with a faster progression to the red-ripe stage. Likewise, it displayed a profound effect on enhancing the seed yield contributing attributes such as fruit count/plant, fruit weight, fruit yield and seed number/fruit. Adoption of a two-stem training system increased the seed yield (kg/ha) by 7.69% with a benefit-cost ratio of 1 : 2.19 as against only 1 : 1.86 in untrained plants. It could be suggested that commercial seed production of indeterminate tomato could be improved by the two-stem training under open-field conditions.Bangladesh J. Bot. 55(2): 341-346, 2026 (June)